Understanding patient demand for and use of antibiotics for upper respiratory tract infection: A qualitative application of the Necessity-Concerns Framework in Saudi Arabia - Almeshal, Nouf; Foot, Holly; Clarke, Amy Louise; Chan, Amy Hai Yan; Horne, Rob (Frontiers in Pharmacology, 2024)
Background: Reducing antimicrobial resistance (AMR) is a priority for public health. Inappropriate patient demand is an important driver of unnecessary antibiotic use (Rezal et al., 2015). To develop an effective intervention to reduce inappropriate demand for antibiotics in upper respiratory tract infections (URTIs), it is important to identify patient perceptions that influence demand for, and appropriate use of antibiotics.To identify and describe the beliefs about antibiotics necessity and concerns that patients with URTIs have, in Riyadh, Saudi Arabia.Method: An exploratory qualitative approach was used. One-to-one, face-to-face or telephone semistructured interviews were conducted with participants recruited using purposive sampling (based on age and gender) from primary healthcare centre in Riyadh, Saudi Arabia were conducted. Only adult patients who currently experience URTIs symptoms and agreed to participate were recruited.Recruitment for interviews continued until data saturation point was reached. The interview guide explored patients' necessity beliefs and concerns about antibiotics, AMR perceptions, and expectations from URTIs consultation. Interview transcripts were coded using QSR NVivo 12 using framework analysis informed by the Necessity-Concerns Framework to identify key motivations driving antibiotic requests and consultations.Results: the study interviewed 32 participants (44% were male, average age was 36.84). Results identified that the patients often relate their personal need for antibiotics when encountering an URTIs symptoms to the type, severity and duration of symptoms. Patients also linked antibiotics with quicker recovery, generally expressing few concerns about antibiotics mainly because of its short duration of use. However, some conveyed their concern about frequent administration of antibiotics and effect on the body's immune system function, which may make them more prone to infections in the future.Participants varied widely in their awareness of AMR; this was associated with many misconceptions, such as confusing AMR with antibiotics efficacy and tolerance. Interestingly, the interplay between necessity beliefs and concerns was observed to influence the decision to start and stop antibiotic, potentially impacting inappropriate antibiotic demand and unnecessary use.This study highlighted important beliefs and misconceptions about antibiotics and AMR in Saudi population which can be targeted in future interventions to reduce inappropriate demand for antibiotics and optimise appropriate usage.